The Influence Of Professional Ethics, Locus Of Control, And Work Experience On Ethical Decision-Making Among Tax Consultants, With Religiosity As A Moderating Variable - Diah Nurlaeni; Juita Tanjung (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to examine the effects of professional ethics, locus of control, and work experience on tax consultants’ ethical decision-making and to investigate the moderating role of religiosity. A quantitative approach was employed, with data collected through questionnaires distributed to tax consultants and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method with SmartPLS 4.0. The results indicate that professional ethics, locus of control, and work experience have a positive and significant influence on ethical decision-making. Furthermore, religiosity significantly moderates the relationships between professional ethics, locus of control, work experience, and ethical decision-making. These findings suggest that stronger professional ethics, greater self-control, broader work experience, and higher religiosity encourage tax consultants to make more ethical and responsible decisions in accordance with professional codes of conduct and applicable tax regulations. The study contributes to the development of tax and professional ethics literature and provides practical insights for improving ethical decision-making among tax consultants.